Oral Films Printed with Green Propolis Ethanolic Extract - Remedio, Leandro Neodini; Garcia, Vitor Augusto dos Santos [UNESP]; Rochetti, Arina Lazaro; Berretta, Andresa Aparecida; Ferreira, Julieta Adriana; Fukumasu, Heidge; Vanin, Fernanda Maria; Yoshida, Cristiana Maria Pedroso; de Carvalho, Rosemary Aparecida (MDPI, 2024)
Oral film (OF) research has intensified due to the effortless administration and advantages related to absorption in systemic circulation. Chitosan is one of the polymers widely used in the production of OFs; however, studies evaluating the maintenance of the active principles’ activity are incipient. Propolis has been widely used as an active compound due to its different actions. Printing techniques to incorporate propolis in OFs prove to be efficient. The objective of the present study is to develop and characterize oral films based on chitosan and propolis using printing techniques and to evaluate the main activities of the extract incorporated into the polymeric matrix. The OFs were characterized in relation to the structure using scanning and atomic force electron microscopy; the mechanical properties, disintegration time, wettability, and stability of antioxidant activity were evaluated. The ethanolic extract of green propolis (GPEE) concentration influenced the properties of the OFs. The stability (phenolic compounds and antioxidant activity) was reduced in the first 20 days, and after this period, it remained constant.
Keywords: printing layers; roughness; stability; tape casting